Direct and indirect relationships between genetic diversity of a dominant grass, community diversity and above‐ground productivity in tallgrass prairie. (1st August 2013) - Chang, Cynthia C.; Smith, Melinda D.; Prinzing, Andreas
Abstract Question Both genetic diversity within a dominant species and species diversity have been shown to affect productivity. However, these two levels of diversity have the potential to affect productivity in similar or opposing ways. Our study assessed direct and indirect relationships between genetic diversity of a dominant grass species and plant community diversity on productivity within a mesic grassland with naturally co‐occurring genotypes and species. Location Konza Prairie Biological Station, Kansas, USA (39°05′35″ N, 96°33′31″ W). Methods We conducted a study at two sites (~65 plots per site) in intact tallgrass prairie that have been subjected to frequent (burned 14 times) and infrequent (burned nine times) fire treatments for ~30 yrs. With frequent burning, the dominant C4 grass, Andropogon gerardii, typically has higher abundance; in contrast, infrequently burned sites typically have higher species diversity but lower abundance of A. gerardii. Therefore, we hypothesized that genetic diversity within A. gerardii would have a significant direct relationship with productivity for the frequently burned site due to higher population abundances of A. gerardii overall, whereas species diversity would have a significant direct relationship with productivity for the infrequently burned site. Results Contrary to our predictions, genetic diversity of A. gerardii was not related to above‐ground productivity either directly or indirectly via traits, while diversity at the community level had a negative indirect relationship with productivity via a negative effect of A. gerardii abundance on community diversity for both frequently and infrequently burned sites. Conclusions While much of the focus of diversity–productivity research has been on direct relationships between diversity at the community or population level separately, future studies should examine the indirect and potentially interactive effects of both levels of diversity in natural communities.